Mothering and Desistance in Re-Entry - Michalsen, Venezia (Routledge, 2018)
Although there is plentiful research on the impact of marriage, employment and the military on desistance from criminal behaviour in the lives of men, far less
Keywords: dept.soc

Great Expectations: The Sociology of Survival and Success in Organized Team Sports - Doob, Christopher B. (Routledge, 2018)
Keywords: dept.soc

Justice for the Poor: A Study of Criminal Defence Work - Emmelman, D.S. (Taylor and Francis, 2018)
This title was first published in 2003. In this study, the author examines the behavior of one group of court-appointed defence attorneys and reaches the conclusion that although, in contrast to popular opinion, these attorneys maintain an adversarial stance against the prosecutors and behave in a legally ethical (or "procedurally just") manner, case outcomes are unduly shaped by social class and are therefore substantively unjust. This occurs because poor defendants typically lack cultural rhetoric that favourably influences those who construct and operate the criminal court system. Ironically, this indicates that, in many cases, the process of plea bargaining may be more substantively just than trials. A major contribution of the study is the detailed analysis of the manner by which oppression and substantive injustice occur in the adjudication of many cases and how the cultural practices of the powerful can frequently misconstrue, exclude and mute the voices of the poor. © Debra S. Emmelman 2003.
Journal Abbreviation: Justice for the Poor: A Study of Criminal Def. Work Pages: 153 Publication Title: Justice for the Poor: A Study of Criminal Def. Work
Keywords: dept.soc

A life-course perspective on incarcerated women’s views on adulthood - Umamaheswar, Janani (Women & Criminal Justice, 2018)
2 citations (Crossref) [2023-10-31]
Keywords: dept.soc; peer-reviewed

Studying homeless and incarcerated persons: A comparative account of doing field research with hard-to-reach populations - Umamaheswar, Janani (Forum Qualitative Sozialforschung, 2018)
In this article, I discuss the process of conducting research with two vulnerable and hard-to-reach populations (homeless and incarcerated men) in three research locations characterized by varying levels of gatekeeping: a prison, public streets in an urban city, and a residential facility for homeless men. I argue that, despite the obstacles to independent research that gatekeepers (officials who can grant or deny researchers access to participants) pose, research with vulnerable, hard-to-reach populations in different field sites reveals some of the benefits of using field sites characterized by gatekeeping and strict rules to which researchers must adhere. Many of these benefits, however, go unacknowledged in discussions of access in qualitative studies—especially in the penological literature. I conclude that, instead of shying away from qualitative prison studies, researchers should take advantage of the benefits that prisons offer as field sites.
Citation Key Alias: lens.org/135-139-935-744-665, pop00300
Keywords: Access; Feldforschung; Field research; Gatekeeping; Gefängnis; Gefängnisforschung; Grounded theory methodology; Grounded-Theory-Methodologie; Homelessness; Interviewing; Interviews; Obdachlosigkeit; Prison; Prison research; Zugang; access; dept.soc; field research; gatekeeping; grounded theory methodology; homelessness; interviewing; peer-reviewed; prison; prison research

Book Review: 'Connecting in college: How friendship networks matter for academic and social success' by J. M. McCabe - Kenty-Drane, Jessica L. (American Journal of Sociology, 2018)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000434407000030 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: book.review; dept.soc; peer-reviewed

Navigating the evidentiary turn in public health: Sensemaking strategies to integrate genomics into state-level chronic disease prevention programs - Senier, Laura; Smollin, Leandra; Lee, Rachael; Nicoll, Lauren; Shields, Michael; Tan, Catherine (Social Science & Medicine, 2018)
1 citations (Crossref) [2023-10-31]
Keywords: dept.soc; peer-reviewed

“I'm a normal autistic person, not an abnormal neurotypical”: Autism Spectrum Disorder diagnosis as biographical illumination - Tan, Catherine D. (Social Science & Medicine, 2018)
40 citations (Crossref) [2023-10-31]
Keywords: dept.soc; peer-reviewed